2003
DOI: 10.2214/ajr.180.5.1801265
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Normal and Hyperplastic Thymus on Chemical-Shift MR Imaging

Abstract: The thymic tissue revealed homogeneous decrease in intensity on opposed-phase MR images relative to that seen on in-phase images in 15 healthy volunteers and two patients with hyperplastic thymus. Chemical-shift MR imaging may be useful in identifying normal thymic tissue and the hyperplastic thymus in early adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 10 publications
0
48
0
Order By: Relevance
“…In patients with enlarged thymus older than 15 years of age, chemical shift MRI can diagnose thymic hyperplasia by detecting fatty infiltration within the thymus and is useful in its differentiation from neoplastic processes (15,16). In a series of 41 patients consisting of 23 thymic hyperplasia and 18 thymic neoplasm, chemical shift MRI could differentiate thymic hyperplasia from thymic neoplasms in all patients.…”
Section: Thymic Hyperplasia and Thymic Reboundmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with enlarged thymus older than 15 years of age, chemical shift MRI can diagnose thymic hyperplasia by detecting fatty infiltration within the thymus and is useful in its differentiation from neoplastic processes (15,16). In a series of 41 patients consisting of 23 thymic hyperplasia and 18 thymic neoplasm, chemical shift MRI could differentiate thymic hyperplasia from thymic neoplasms in all patients.…”
Section: Thymic Hyperplasia and Thymic Reboundmentioning
confidence: 99%
“…A recent report suggested chemical shift MRI to be beneficial in differentiation of thymomas from thymic hyperplasia in non-MG patients (15,16). MRI may provide similar results also in MG patients.…”
Section: Thymomamentioning
confidence: 99%
See 1 more Smart Citation
“…A unique method for characterizing the normal and hyperplastic thymus with chemical-shift MRI was reported recently (13). In that method, chemical-shift MRI is used to demonstrate the presence of intravoxel fat and water within the tissue and to distinguish normal from abnormal thymus by qualitative comparison and by calculating the chemical-shift ratio between inphase and opposed-phase gradient-echo images (13).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that chemical-shift MRI is useful for characterizing the normal thymus in early adulthood, and for diagnosing thymic hyperplasia by detecting the intravoxel fat and water within the thymus (13). According to the anatomical literature, a microscopic amount of fatty tissue exists within the thymus at birth, and normal fatty replacement of the thymus primarily starts at about 10 years of age, before the thymus undergoes obvious morphologic involution (14,15).…”
mentioning
confidence: 99%